A policy to boost R&D: Does the R&D tax credit work? - Damien Ientile; Jacques Mairesse (EIB Papers, 2009)
In this article we address various issues raised by the evaluation of the R&D tax credit policy. We first consider the studies that estimate the direct effects of the tax credit on R&D inputs. We discuss results obtained through different approaches and methods and show that they give a contrasted picture of the policy's effectiveness. Next we argue that a comprehensive evaluation of the R&D tax credit should include other outcomes and present studies focussing on them. We also initiate a very tentative meta-analysis to obtain a more synthetic view on the various evaluation results. We finally conclude that harmonization and increased comparability in evaluation studies would be useful to bridge the gap between evaluation and policy design and implementation.
Keywords: 330; Forschungssubvention; Steuerbegünstigung; Forschungs- und Technologiepolitik; Wirkungsanalyse; Publikationsanalyse